Commercial cattle producers: bull selection criteria - D.D. Simms; J.M. Geske; R.P. Bolze (Kansas Agricultural Experiment Station Research Reports, 1994)
A survey of 312 commercial cattle producers was conducted to determine the relative importance of selection criteria used in buying bulls. Calving ease was a major consideration of a high percentage of producers, and individual performance was being emphasized more than expected progeny differences (EPDs). Only 23% of the producers included EPDs in their first three selection criteria. Visual appraisal focused on structural soundness, length, and muscling.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Bulls; Selection; Breeding; Expected progeny differences